Corporate Social Responsibility in Nigeria’s Oil Industry: Governance Gaps and Implications for National Security and Development - Abdul-Hamid, O. Y. (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
The discovery of oil in Nigeria drastically transformed its economy and international trade system. However, rather than fostering national prosperity, it has left much of the population in poverty and worsened the country’s infrastructure. This challenge is compounded by the insufficient Corporate Social Responsibility (CSR) efforts from oil companies, resulting in recurring crises, civil unrest, and escalating violence within the oil-producing regions, which has national repercussions and poses a threat to security. This paper explores the impact of CSR shortcomings by oil corporations on Nigeria’s national security and development. A qualitative research approach is used, drawing on primary sources and secondary sources. Findings reveal a lack of coherent policy or legislation on CSR in Nigeria, underscoring the need for stronger regulatory frameworks and closer scrutiny of oil companies' CSR initiatives. The study recommends engaging genuine stakeholders and local community members in CSR project planning and implementation to ensure relevance, continuity, and meaningful impact on beneficiaries.